Identification of production problems of small-scale garment manufacturers a comparative study - Sabas, Donnah Mae S.; Arribas, Lydia B. (1999.)
Production function is the heart of every manufacturing industry. The study aims to help the industry improve their production efficiency, especially the small-scale garment industry. It underscores the importance of creating an efficiently operating production to the manufacturer and indirectly to the whole local garment industry. specifically, the problem of the study is: What are production problems common to garment manufacturers and what problems are unique to each, given two similar manufacturers. It tried to determine he causes and effects of these problems on the input and output efficiency of production. Data were gathered through interviews and observations. Respondents were the production managers, sewing supervisors and quality controllers of the two subject manufacturers. The collected data were matched and compare to see the similarities and differences from the two companies' production problems. This study proved its hypotheses true. It has proven that manufacturers with similar characteristics, like their product lines and production flow, have a lot of similar production problems but still have problems unique to one manufacturer. The number one factor that was responsible for the uniqueness of the problem to a manufacturer, especially in this labor-intensive industry. The paper worked along the elimination of these problems which would greatly improve the production efficiency of the factory, therefore increasing its capacity in order to be able to serve.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing factories -- Philippines